A rapid indicator-based assessment of foreign resident preparedness in Japan during Typhoon Hagibis. (December 2020) - Dasgupta, Rajarshi; Basu, Mrittika; Kumar, Pankaj; Johnson, Brian Alan; Mitra, Bijon K.; Avtar, Ram; Shaw, Rajib
Abstract: The paper narrates a pilot study to understand disaster preparedness among foreign residents living in Japan, using typhoon Hagibis as a reference. We empirically evaluated an individual disaster preparedness framework following the 72-h golden rule of disaster survival. The framework consisted of 14 variables, and responses were collected over a five-point Likert scale. In addition, six perceptive variables, which provided a self-evaluation of disaster preparedness against the native Japanese population, were also administered to 133 foreign residents. The data were subjected to exploratory factor analysis and multiple linear regression modeling to understand the thematic dimensions and association of perceptive variables that contribute towards disaster preparedness. Our results indicated three interlinked dimensions, namely, (a) Emergency preparation and awareness (b) Experiential learning, and (c) Training and exposure. Of these, 'Emergency preparation and awareness' and "Training and exposure" showed a statistically significant and positive association with several perceptive variables (particularly, the ability to seek neighborhood help, participation in community events, and the ability to receive local level disaster information). The paper concludes with several recommendations, of which, building a local support network for foreign residents and to disseminate local disaster-related information remains critical.